release film
Patent Information
- Application Number
- CN202580020820.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-15
- Filing Date
- 2025-03-12
- Publication Date
- 2026-10-27
AI Technical Summary
[0053]本发明的脱模薄膜能够提高脱模层的剥离性和润湿性,进而能够抑制薄层的树脂片、特别是陶瓷生片的缺陷的产生。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to a release film having a substrate film and a release layer, and to a release film useful as a film for various processes. Background Technology
[0002] Previously, release films with a release layer laminated on top of a polyester film or similar substrate have high heat resistance and mechanical properties, and are used in the process of making resin sheets such as adhesive sheets, cover films, ceramic green sheets, and polymer electrolyte films. In addition, as a release layer for release films, many release layers formed from coating compositions containing organosilicon have been proposed due to their good heat resistance and peelability (for example, Patent Documents 1-5).
[0003] The aforementioned release film is also used as an engineering film for forming ceramic green sheets that require high smoothness, such as ceramic capacitors and ceramic substrates. In recent years, with the miniaturization and increasing capacitance of multilayer ceramic capacitors, there has been a trend towards thinner ceramic green sheets. Ceramic green sheets are formed by coating a slurry containing ceramic components such as barium titanate and binder resin onto the release layer of the release film and then drying it. Multilayer ceramic capacitors are manufactured by laminating, pressing, firing, and coating external electrodes on the electrode-bearing ceramic green sheets obtained by printing electrodes on the formed ceramic green sheets and peeling them off from the release film.
[0004] Patent documents 1-2 propose a release film produced by the following method (hereinafter referred to as "offline coating"): a coating composition containing a polysiloxane having unsaturated groups, a polysiloxane having hydrogen groups, a platinum group metal catalyst, and an organic solvent is coated onto one side of a biaxially stretched polyester, and then heat-treated to dry and cure the coating composition to form a release layer.
[0005] Patent document 3 discloses a release film, which forms a release layer by coating an aqueous coating composition containing alkenyl organosilicon and organosilicon containing hydrogen and phenyl groups onto one side of a polyester film and then stretching the polyester film (hereinafter referred to as "online coating").
[0006] Furthermore, Patent Document 4 discloses a release film that uses a coating composition containing an aryl silicone to form a release layer through offline coating. Moreover, Patent Document 5 discloses a release film that uses a coating composition containing an silicone having Q units to form a release layer through online coating.
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent Application Publication No. 2003-292894
[0010] Patent Document 2: International Publication No. WO2017 / 200056
[0011] Patent Document 3: Japanese Patent No. 5735278
[0012] Patent Document 4: Japanese Patent No. 5756315
[0013] Patent Document 5: Japanese Patent Application Publication No. 2021-11081 Summary of the Invention
[0014] The problem the invention aims to solve
[0015] In recent years, with the thinning of ceramic green sheets, there has been a growing demand for release films that can peel off ceramic green sheets with low and uniform force. Additionally, release films with good wetting properties for the ceramic slurry coated on the release layer are required. To achieve thin-film ceramic green sheets, it is necessary to uniformly coat the release layer with a low-solids-content ceramic slurry diluted with an organic solvent in an amount greater than or equal to resin. However, when a ceramic slurry composed of such a composition is coated onto the release layer, the wetting property of the release film on the ceramic slurry sometimes becomes insufficient. Due to micro-pinholes and uneven coating caused during coating, pinholes and uneven thickness may occur in the ceramic green sheet, potentially worsening the yield of multilayer ceramic capacitors.
[0016] Furthermore, the release film requires a high degree of adhesion to the substrate. For example, if the substrate adhesion of the release film is insufficient, during the peeling of various resin sheets laminated on the release film, part or most of the release film may detach from the substrate, and components of the release film may become mixed into the resin sheets. Additionally, during the various resin sheet molding processes and the release film transport process, defects such as the release film peeling off from the substrate film may occur.
[0017] Furthermore, the release film requires excellent adhesion to the substrate immediately after the release layer is formed, i.e., immediate adhesion to the substrate. In the absence of a release layer with immediate adhesion to the substrate, during the manufacturing process, a portion of the release layer may transfer onto the conveyor rollers. When the release film is wound into a roll, the release layer may also transfer to the back side of the release film that is in contact with it. If this transfer occurs to the conveyor rollers or the back side of the release film, it leads to deterioration of the coating uniformity of the release layer, reduction in the release layer thickness, and surface defects, potentially resulting in re-peeling.
[0018] Patent documents 1 and 2, in particular, indicate that the peelability and wettability of thin-layer ceramic green sheets are insufficient, requiring further consideration of both light peelability and good wettability. Furthermore, since coating compositions containing organic solvents in their main components are used, issues arise regarding the adverse effects on human health caused by contact with the organic solvents and the absorption of their vapors, as well as the environmental impact caused by the release of organic solvent vapors into the atmosphere.
[0019] In addition, the following situations become problems: the drying equipment for organic solvents needs to be explosion-proof, incurring initial setup costs; and the operation requires a large amount of energy, resulting in high CO2 emissions and a heavy environmental impact.
[0020] Patent Document 3 describes a release film with a release layer formed by online coating, but it is not intended for use in forming ceramic green sheets, especially as it presents problems with the peelability of thin ceramic green sheets. Furthermore, a crosslinking agent containing phenyl is used to improve the adhesion between the substrate and the release layer, but the effect of phenyl on the peel force has not been confirmed, making it unsuitable as a release film exhibiting light peelability.
[0021] Patent Document 4 describes a release film formed by an aryl-containing siloxane and a crosslinking agent. However, in the invention described in Patent Document 4, there are issues with adverse effects on human health and high environmental impact during the manufacturing process. Furthermore, due to the presence of bulky substituents such as aryl groups, the curing reaction of the release layer is difficult due to their steric hindrance. As described in the examples, when the coating composition is cured at 135°C, the curing heat of the release layer becomes insufficient, potentially negatively affecting peelability. To further cure the release layer, it is necessary to cure it at a higher temperature. However, in the invention described in Patent Document 4, thermal deformation of the substrate film may occur during the manufacturing process, necessitating manufacturing at a lower temperature.
[0022] The release film described in Patent Document 5 is formed by online coating, achieving both peelability and wettability. For example, the development of technology involving thin-layer ceramic green sheets has been ongoing, with demands for further improvements in light peelability and adaptability to thin-layer ceramic green sheets compared to the application of Patent Document 5. Furthermore, there is a demand for improved substrate adhesion of the release layer, and for reducing adverse effects such as re-peeling caused by the release layer detaching from the substrate film during the manufacturing process of the release film and the molding process of resin sheets, such as ceramic green sheets. Particularly when using silicone resins with Q-units, the release layer formation is difficult to follow during substrate film stretching, and the substrate adhesion may deteriorate due to the stress difference between the release layer and the substrate film.
[0023] This invention was made against the backdrop of the prior art. Specifically, the object of this invention is to provide a release film that reduces the amount of organic solvents that are harmful to the human body and have adverse environmental impacts, while achieving a balance between easy peeling and good wettability of thin resin sheets, particularly thin ceramic green sheets, thereby improving the adhesion, especially the immediate adhesion, between the substrate film and the release layer.
[0024] Solution for solving the problem
[0025] In order to solve the above-mentioned problems, the inventors conducted in-depth research and found that the aforementioned objectives could be achieved by using a release film having the following structure, thus completing the present invention.
[0026] That is, the present invention comprises the following components. [1]
[0028] A release film having a release layer on at least one side of a polyester film.
[0029] The aforementioned release layer is a layer formed by reacting and curing the water-based coating composition.
[0030] The aforementioned aqueous coating composition contains an organosilicon emulsion comprising the following resins.
[0031] The aforementioned aqueous coating composition also contains a substrate adhesion promoter.
[0032] (a) A first resin having a siloxane structure as shown in Formula 1,
[0033]
[0034] (In structural formula 1, R1 is an alkenyl group with 2 or more but less than 8 carbon atoms, R2 is an alkyl group with 1 to 4 carbon atoms or an alkenyl group with 2 or more but less than 8 carbon atoms, and k is 1 or more but less than 50).
[0035] (b) The second resin, which contains hydrogen groups; and
[0036] (c) The third resin, which contains SiO 4 / 2 The Q unit shown is an organosilicon. [2]
[0038] According to the release film described in [1], the aforementioned substrate adhesion agent is a water-soluble or water-dispersible silane coupling agent having hydrolyzable groups and organic functional groups directly or by means of linking groups bonded to silicon atoms. [3]
[0040] According to the release film described in [1] or [2], wherein,
[0041] The aforementioned (a) first resin and / or the aforementioned (b) second resin also have a siloxane structure as shown in structural formula 2 below.
[0042]
[0043] (In structural formula 2, R3 is an alkyl group with 1 to 4 carbon atoms, Ar is an aryl group, and m is 1 or more and 50 or less). [4]
[0045] The release film according to any one of [1] to [3], wherein the second resin of (b) above has the structure shown in the following chemical formula 2.
[0046]
[0047] (In chemical formula 2, l is 1 or more and less than 50, m is 1 or more and less than 50, and n is 0 or more and less than 5.) [5]
[0049] According to any one of [1] to [4], the release film is formed as follows: the aforementioned aqueous coating composition is coated on a substrate film before crystal orientation is completed, stretched in at least one direction, and then heat-treated to complete the crystal orientation of the substrate film, thereby forming the release film. [6]
[0051] The release film according to any one of [1] to [5], wherein the aforementioned release film is a release film for manufacturing ceramic capacitors or for manufacturing resin sheets.
[0052] The effects of the invention
[0053] The release film of the present invention can improve the peelability and wettability of the release layer, thereby suppressing the generation of defects in thin resin sheets, especially ceramic green sheets.
[0054] This reduces the harm to human health and environmental impact during the manufacturing process. Furthermore, it allows for the formation of a release layer that eliminates concerns about the adhesion between the substrate film and the release layer, particularly regarding the immediate deterioration of the adhesion to the substrate. Detailed Implementation
[0055] The present invention has the features described in this specification, and therefore can further solve the problems described below and achieve the desired effect.
[0056] In particular, it can further balance the light peelability and good wettability of thin-layer ceramic green sheets. Furthermore, compared to coating compositions that contain organic solvents in their main components, it can significantly reduce the amount of organic solvents, or even eliminate them entirely. As a result, it can significantly reduce the adverse effects on human health caused by contact with organic solvents and inhalation of vapors, as well as the environmental burden caused by the release of organic solvent vapors into the atmosphere.
[0057] Furthermore, the drying equipment for organic solvents does not need to be explosion-proof, and energy consumption can be reduced during operation compared to conventional manufacturing equipment. Therefore, CO2 emissions can also be reduced, thus minimizing environmental impact.
[0058] Furthermore, according to the present invention, by using an organosilicon emulsion comprising an organosilicon resin with a specific structure and composition, a release film with superior peelability compared to conventional release films manufactured by online coating can be provided. In particular, by forming a release layer comprising a cured organosilicon having Q units, a release film with excellent peelability and wettability can be produced. Additionally, by forming a release layer comprising a cured organosilicon also containing an aryl siloxane structure, light peelability can be improved. Furthermore, a release film with excellent substrate adhesion can also be produced.
[0059] Furthermore, according to the present invention, since an aqueous coating composition containing a substrate adhesion promoter is used, a release film with excellent substrate adhesion can be produced. In particular, when manufacturing a release layer containing an organosilicon resin having Q units by online coating, there is a difference in tensile strength between the substrate film and the release layer formation, requiring immediate adhesion to the substrate immediately after the release layer has cured.
[0060] According to the present invention, by including a substrate adhesion promoter, a release film with excellent immediate adhesion to a substrate can be produced.
[0061] The present invention will now be described in detail. The present invention relates to a release film having a release layer on at least one side of a polyester film, wherein the release layer is a layer formed by reacting and curing an aqueous coating composition, the aqueous coating composition comprising an organosilicon emulsion, the organosilicon emulsion comprising the following substances, and the aqueous coating composition further comprising a substrate adhesion promoter.
[0062] (a) The first resin having a siloxane structure as shown in Formula 1.
[0063]
[0064] (In structural formula 1, R1 is an alkenyl group with 2 or more but less than 8 carbon atoms, R2 is an alkyl group with 1 to 4 carbon atoms or an alkenyl group with 2 or more but less than 8 carbon atoms, and k is 1 or more but less than 50).
[0065] (b) The second resin, which contains hydrogen groups;
[0066] (c) The third resin, which contains SiO 4 / 2 The Q unit shown is an organosilicon.
[0067] The present invention, with such a configuration, can balance the light peelability and good wettability of the release layer, and can provide a defect-free and uniform thickness for thin resin sheets, such as thin ceramic green sheets, and can suppress defects such as pinholes.
[0068] In addition, the present invention can achieve the following effects. In the present invention, since an aqueous coating composition with significantly reduced organic solvents or an aqueous coating composition that is substantially free of organic solvents is used compared with the past, it is less harmful to the human body and has less environmental impact, and can produce a release film while suppressing the generation of CO2.
[0069] Furthermore, in one embodiment, the release film of the present invention is formed by coating an aqueous coating composition comprising an organosilicon emulsion having a defined composition in an online coating manner to form a release layer, thereby producing a release layer with excellent substrate adhesion in addition to peelability and wettability. More specifically, by comprising an organosilicon emulsion containing organosilicon having Q units, a structure with three-dimensionally expanded siloxane bonds can be adopted. Therefore, by crosslinking between the alkenyl group in the organosilicon molecule having Q units and the organosilicon having hydrogen groups, a dense crosslinked structure can be adopted, resulting in a release layer with excellent solvent resistance and exhibiting light peelability. Furthermore, by containing Q units, the hydrophobicity of the release layer surface is reduced, enabling the production of a release layer with excellent wettability.
[0070] Furthermore, by incorporating an organosilicon emulsion containing organosilicon with an aryl siloxane structure, the adhesion between the substrate film and the release layer can be improved through intermolecular interactions between the aryl groups. Moreover, by using a bulky substituent such as an aryl group, the curing reaction of the release layer can be delayed, allowing the substrate film to undergo curing before stretching, and only after the crystal orientation is complete following stretching, without undergoing a curing reaction. By preventing curing during the stretching of the substrate film, stress caused by the difference in stretchability between the substrate film and the coating composition can be reduced, preventing a decrease in substrate adhesion.
[0071] In particular, by including the first resin, the second resin and the third resin in this invention, the above-mentioned effects can be achieved more effectively.
[0072] This invention improves the substrate adhesion of the release layer by utilizing the reaction delay effect based on aryl groups. For example, to improve the substrate adhesion of the release layer, it is preferable to perform the curing reaction after stretching the substrate film.
[0073] Furthermore, by using an aqueous coating composition containing a substrate adhesion promoter, a release layer with excellent immediate adhesion to the substrate immediately after its formation can be produced. This excellent immediate adhesion, for example, prevents part or most of the release layer from detaching from the substrate when various resin sheets laminated on the release film are peeled off. Therefore, the problem of release layer components contaminating the resin sheets can be avoided. Additionally, during various resin sheet molding processes, the release layer can also be prevented from peeling off from the substrate film during the release film transport process.
[0074] Furthermore, due to its excellent immediate adhesion to the substrate, the present invention can suppress the transfer of a portion of the release layer to the conveyor roller during the manufacturing process of the release film, and can avoid the risk of the release layer transferring to the back side of the release film that is in contact with the release layer when the release film is rolled into a roll.
[0075] If the release layer is transferred to the conveyor roller or the back of the release film, the uniformity of the release layer coating will deteriorate, the thickness of the release layer will decrease, and defects will appear on the surface of the release layer, which may lead to re-peeling. Therefore, the present invention can solve such problems.
[0076] In this invention, immediate adhesion refers to the adhesion of the release layer to the substrate immediately after the release layer is formed using the water-based coating composition, for example, the adhesion within the range of 1 second to 24 hours after the release layer is formed.
[0077] In addition, the instantaneous seal can be measured after the film is rolled into a roll.
[0078] Here, as will be described later, it is structurally difficult to determine the orientation state and distribution of the resin components in the release layer, the distribution of substituents that contribute to peelability on the surface of the release layer, etc. In this invention, it is found that "it is best to carry out the curing reaction after the substrate film is stretched".
[0079] (Polyester film)
[0080] The polyester constituting the polyester film used as the substrate film is not particularly limited, and any polyester commonly used as a substrate for release films can be used for film forming. Preferably, it is a crystalline linear saturated polyester formed from aromatic diacid components and glycol components, such as polyethylene terephthalate, polyethylene 2,6-naphthalenedicarboxylate, polyethylene terephthalate, polyethylene terephthalate, propylene terephthalate, or copolymers with components of these resins as the main components. Polyester films formed from polyethylene terephthalate are particularly preferred. In polyethylene terephthalate, the repeating unit of polyethylene terephthalate is preferably 90 mol% or more, more preferably 95 mol% or more, and small amounts of other dicarboxylic acid components and glycol components may also be copolymerized. For example, from a cost point of view, it is preferable to manufacture it only from terephthalic acid and ethylene glycol. Furthermore, known additives, such as antioxidants, light stabilizers, ultraviolet absorbers, crystallizing agents, etc., can be added to a extent that does not impair the effect of the release film of the present invention. Considering the high elastic modulus in both directions, the polyester film is preferably a biaxially oriented polyester film.
[0081] The intrinsic viscosity of the aforementioned polyester film is preferably 0.50 dl / g or higher and 0.70 dl / g or lower, more preferably 0.52 dl / g or higher and 0.62 dl / g or lower. When the intrinsic viscosity is 0.50 dl / g or higher, significant breakage does not occur during the stretching process, which is preferred. Conversely, when the intrinsic viscosity is 0.70 dl / g or lower, the cutability is good when cutting to the specified product width, and dimensional defects are not produced, which is also preferred. Furthermore, the raw material granules are preferably thoroughly vacuum dried.
[0082] It should be noted that in this specification, when referred to only as "polyester film", it sometimes refers to a polyester film having (layered) surface layer A and surface layer B.
[0083] The method for manufacturing the polyester film in this invention is not particularly limited, and conventionally used methods can be used. For example, the aforementioned polyester can be melted in an extruder, extruded into a film, cooled on a rotary cooling drum to obtain an unstretched film, and then biaxially stretched to obtain the film. The biaxially stretched film can be obtained by sequentially biaxially stretching a longitudinally or transversely uniaxially stretched film in the transverse or longitudinal direction, or by simultaneously biaxially stretching an unstretched film in both the longitudinal and transverse directions.
[0084] In this invention, the stretching temperature during polyester film stretching is preferably set to be above the secondary transformation point (Tg) of the polyester. Preferably, the stretching is performed at a ratio of 1 to 8 times, particularly 2 to 6 times, in both the longitudinal and transverse directions.
[0085] The thickness of the aforementioned polyester film is preferably 12 μm or more and 50 μm or less, more preferably 15 μm or more and 38 μm or less, and even more preferably 19 μm or more and 33 μm or less. If the film thickness is 12 μm or more, deformation due to heat is not a concern during film production, processing, or molding, which is preferable. On the other hand, if the film thickness is 50 μm or less, the amount of waste film after use will not increase drastically, which is preferable in terms of reducing environmental impact.
[0086] The aforementioned polyester film substrate can be a single layer or a multilayer consisting of two or more layers. For example, the substrate film can be a polyester film having a surface layer A that substantially does not contain particles with a particle size of 1.0 μm or larger and a surface layer B that contains particles. Preferably, surface layer A substantially does not contain inorganic particles with a particle size of 1.0 μm or larger.
[0087] In this method, surface layer A may contain particles with a diameter of less than 1.0 μm and greater than 1 nm. By making surface layer A substantially free of particles with a diameter of 1.0 μm or greater, such as inorganic particles, it is possible to reduce defects caused by the transfer of particle shapes from the substrate to the resin sheet.
[0088] In one approach, surface layer A, by being free of particles smaller than 1.0 μm, can more effectively suppress the transfer of particle shapes from the substrate to the resin sheet, thus preventing defects.
[0089] In one embodiment, the aforementioned polyester film substrate is preferably a laminated film having a surface layer A that is substantially free of inorganic particles on at least one side. This more effectively suppresses defects caused by the transfer of particle shapes from the substrate to the resin sheet. For example, the surface layer A, which is substantially free of particles with a particle size less than 1.0 μm, is preferably also substantially free of particles with a particle size greater than 1.0 μm.
[0090] In this invention, "substantially free of particles" means, for example, in the case of inorganic particles smaller than 1.0 μm, that the content is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit when quantifying inorganic elements by fluorescence X-ray analysis. This is because even without actively adding particles to the film, contaminants from foreign matter, raw material resins, or dirt adhering to the production line or equipment during the film manufacturing process can sometimes detach and mix into the film. Furthermore, "substantially free of particles with a diameter of 1.0 μm or larger" means actively free of particles with a diameter of 1.0 μm or larger.
[0091] In the case of a laminated polyester film consisting of two or more layers, it is preferable to have a surface layer B that can contain inorganic particles on the opposite side of the surface layer A, which is substantially free of inorganic particles.
[0092] As a laminated structure, if the layer on the side where the release layer is coated is designated as layer A, the layer on the opposite side is designated as layer B, and the remaining core layers are designated as layer C, then the layer configuration in the thickness direction can be a laminated structure such as release layer / A / B or release layer / A / C / B. Of course, layer C can also be composed of multiple layers. Furthermore, the surface layer B may not contain inorganic particles. In this case, to impart sliding properties for winding the film into a roll, it is preferable to provide a coating containing inorganic particles and a binder on the surface layer B.
[0093] In the polyester film substrate of the present invention, from the viewpoint of film slippage and ease of air expulsion, the surface layer B opposite to the side on which the release layer is formed preferably contains inorganic particles, and silica particles and / or calcium carbonate particles are particularly preferred. The total amount of inorganic particles in the surface layer B is preferably 5000 ppm or more and 15000 ppm or less.
[0094] At this point, the average surface roughness (Sa) of the thin film of surface layer B is preferably in the range of 1 nm or more and 40 nm or less. More preferably, it is in the range of 5 nm or more and 35 nm or less. When the total amount of silica particles and / or calcium carbonate particles is 5000 ppm or more and Sa is 1 nm or more, air can escape uniformly when the film is rolled into a roll, resulting in a good winding shape and good planarity, which is suitable for the manufacture of ultrathin ceramic green sheets. In addition, when the total amount of silica particles and / or calcium carbonate particles is 15000 ppm or less and Sa is 40 nm or less, lubricant aggregation is less likely to occur, and coarse protrusions cannot be formed. Therefore, the quality is stable during the manufacture of ultrathin ceramic green sheets, which is preferred.
[0095] In addition to silica and / or calcium carbonate, inactive inorganic particles and / or heat-resistant organic particles can be used as the particles contained in layer B. However, from the viewpoints of transparency and cost, silica particles and / or calcium carbonate particles are preferred. Other usable inorganic particles include alumina-silica composite oxide particles and hydroxyapatite particles. Heat-resistant organic particles include cross-linked polyacrylic acid particles, cross-linked polystyrene particles, and benzoguanamine particles. When using silica particles, porous colloidal silica is preferred. When using calcium carbonate particles, from the viewpoint of preventing lubricant detachment, light calcium carbonate with a surface treatment using a polyacrylic acid polymer is preferred.
[0096] The average particle size of the inorganic particles added to the surface layer B is preferably 0.1 μm or more and 2.0 μm or less, particularly preferably 0.5 μm or more and 1.0 μm or less. If the average particle size of the inorganic particles is 0.1 μm or more, the release film exhibits good sliding properties, which is preferred. Furthermore, if the average particle size is 2.0 μm or less, there is no concern about adverse effects on the smoothness of the release layer surface, thus eliminating concerns about pinholes forming on the ceramic green sheet, which is also preferred.
[0097] From the perspective of reducing pinholes, in order to prevent the mixing of inorganic particles such as lubricants, it is preferable not to use recycled materials in the layer on the side of the release layer, i.e., surface layer A.
[0098] The thickness ratio of surface layer A, which is the layer on the side where the release layer is provided, is preferably 20% or more and 50% or less of the total thickness of the substrate film. If it is 20% or more, it is less susceptible to the influence of particles contained in surface layer B, etc., from inside the film, and the average surface roughness Sa of the region is more likely to meet the above range, which is preferred. When it is 50% or less of the total thickness of the substrate film, the utilization rate of recycled materials in surface layer B can be increased, resulting in a lower environmental impact, which is also preferred.
[0099] Furthermore, from an economic point of view, layers other than surface layer A (surface layer B or the aforementioned intermediate layer C) may use 50% to 90% by mass of recycled film scraps or plastic bottles. In this case, the type, amount, particle size, and average surface roughness (Sa) of the lubricant contained in layer B should preferably also meet the above-mentioned ranges.
[0100] In addition, in order to improve the adhesion of subsequent coatings such as release layers and prevent static electricity, a coating can be applied to the surface of surface layer A and / or surface layer B on the film before stretching or after uniaxial stretching in the film-making process, or surface treatment can be performed.
[0101] In one approach, a surface-treated, easy-adhesive layer can be provided on the release layer forming surface of the aqueous coating composition to improve adhesion to the release layer. Examples of surface treatments include plasma treatment, corona discharge treatment, ultraviolet treatment, flame treatment, and electron beam / radiation treatment. Examples of easy-adhesive layers include a layer containing the same resin as the substrate film, as well as antistatic agents, pigments, surfactants, lubricants, and anti-blocking agents. When an adhesion-enhancing agent such as a coupling agent is added to the aqueous coating composition, the release layer can achieve sufficient adhesion to the substrate film even without an easy-adhesive layer.
[0102] (release layer)
[0103] In this invention, a release layer is laminated on surface layer A of the substrate film. In this invention, the release layer is a layer formed by reacting and curing an aqueous coating composition, wherein the aqueous coating composition comprises a silicone emulsion and a substrate adhesion promoter, and the silicone emulsion comprises the following substances.
[0104] (a) A first resin having a siloxane structure as shown in Formula 1,
[0105]
[0106] (In structural formula 1, R1 is an alkenyl group with 2 or more but less than 8 carbon atoms, R2 is an alkyl group with 1 to 4 carbon atoms or an alkenyl group with 2 or more but less than 8 carbon atoms, and k is 1 or more but less than 50).
[0107] (b) The second resin, which contains hydrogen groups;
[0108] (c) The third resin, which contains SiO 4 / 2 The Q unit shown is an organosilicon.
[0109] Here, the aforementioned first resin and / or the aforementioned second resin also have the siloxane structure shown in structural formula 2 below.
[0110]
[0111] (In structural formula 2, R3 is an alkyl group with 1 to 4 carbon atoms, Ar is an aryl group, and m is 1 or more and 50 or less.)
[0112] By endowing the release layer with these characteristics, a release film with excellent peelability and wettability can be provided, suppressing defects such as pinholes in resin sheets and ceramic green sheets, and enabling the formation of sheets with uniform film thickness. Furthermore, a release layer with excellent substrate adhesion can be provided, preventing the release layer from detaching during the manufacturing processes of the release film, resin sheets, and ceramic green sheets. Moreover, by forming a release layer from a cured material containing a substrate adhesion promoter, a release layer with excellent immediate adhesion to the substrate can be provided.
[0113] The aqueous coating composition of this invention is a composition containing a silicone emulsion. The silicone emulsion comprises (a) a first resin, (b) a second resin, and (c) a third resin, and in one embodiment, (d) a fourth resin. A silicone emulsion refers to a substance in which these water-insoluble resins are dispersed in water by a surfactant. The silicone emulsion contained in the aqueous coating composition may suitably be one type, or may suitably be two or more types. Furthermore, the silicone emulsion may contain only one type selected from (a) the first resin, (b) the second resin, (c) the third resin, and (d) the fourth resin, or may contain two or more types, and (a), (b), (c), and (d) may all be contained in one silicone emulsion.
[0114] The aqueous coating composition is preferably substantially free of organic solvents, using water as the dispersion medium. By being substantially free of organic solvents, the stability of the silicone emulsion is improved, preventing compositional changes in the aqueous coating composition, resin aggregation in the silicone emulsion, and gelation caused by emulsion breakdown.
[0115] Essentially, "free of organic solvents" means, for example, a content of 10,000 ppm or less, preferably 5,000 ppm or less, more preferably 3,000 ppm or less, and most preferably below the detection limit relative to the total weight of the aqueous coating composition. This is because, even without intentional use of organic solvents, trace amounts of organic solvents used in the polymerization process of the resin contained in the silicone emulsion, the emulsification process of the emulsion, etc., may sometimes remain.
[0116] (a) First resin)
[0117] The (a) first resin contained in the silicone emulsion preferably has the following structure.
[0118]
[0119] (In structural formula 1, R1 is an alkenyl group with 2 or more but less than 8 carbon atoms, R2 is an alkyl group with 1 to 4 carbon atoms or an alkenyl group with 2 or more but less than 8 carbon atoms, and k is 1 or more but less than 50.)
[0120] By using structural formula 1, a crosslinking reaction is carried out between alkenyl groups and organosilicon with hydrogen groups, resulting in a release layer with high crosslinking density and excellent solvent resistance, exhibiting light peelability.
[0121] Examples of alkenyl groups include vinyl, allyl, butenyl, pentenyl, and hexenyl, among which vinyl is particularly preferred.
[0122] As (a) the first resin, for example, the structure shown in the following chemical formula 1 can be exemplified.
[0123]
[0124] In the above chemical formula 1, R1 is an alkenyl group with 2 or more and 8 or less carbon atoms, and R2 is an alkyl group with 1 or more and 4 or less carbon atoms, or an alkenyl group with 2 or more and 8 or less carbon atoms. As R1, vinyl is preferred, and as R2, methyl is preferred. R2 can be the same or different; for example, it is also preferred that the R2 at both ends is methyl, or that the R2 only in the side chain has a vinyl structure. k is a structure that facilitates the crosslinking reaction, preferably 1 or more and 50 or less. o is a structure that facilitates peelability, preferably 1 or more and 500 or less. By making k 1 or more, the crosslinking reaction proceeds; therefore, it is preferred. If it is 50 or less, unreacted alkenyl groups are less likely to remain in the release layer, resulting in excellent peelability. If o is 1 or more, peelability is exhibited; therefore, it is preferred. If it is 500 or less, there is no concern about a decrease in crosslinking density.
[0125] As exemplified by chemical formula 1, from the viewpoint of exfoliation, it is preferable to contain SiO. 2 / 2 The D-unit of the organosilicon is shown. Organosilicones containing D-units typically have siloxane bonds that readily form helical structures. For example, in the case of polydimethylsiloxane, both methyl groups present in the siloxane bond are arranged on the outer side of the molecular chain, thus exhibiting hydrophobicity and becoming a release layer with excellent peelability, which is therefore preferred.
[0126] In one embodiment, the first resin contained in the silicone emulsion preferably also has the following structural formula 2.
[0127]
[0128] (In structural formula 2, R3 is an alkyl group with 1 to 4 carbon atoms, Ar is an aryl group, and m is 1 or more and 50 or less.)
[0129] By using aryl groups, such as those in Structural Formula 2, which have large substituents, the curing reaction of the release layer is delayed, and curing of the release layer ends when the crystal orientation of the substrate film is completed after stretching. This delayed curing reaction makes it difficult for the release layer to cure during substrate film stretching, thereby maintaining the stretch-following properties of the coating composition and eliminating concerns about a decrease in adhesion due to the stress difference between the substrate film and the release layer, which is preferable. Furthermore, the resulting release layer does not exhibit defects such as coating cracking that occur during stretching, and has excellent peelability, making it even more desirable.
[0130] As described above, (a) the first resin can have structural formula 2. In another embodiment, (b) the second resin contained in the silicone emulsion described later can have the structure of structural formula 2 described above. For example, by having (b) the second resin have aryl groups and (a) the first resin not having aryl groups, in at least one step during the stretching of the substrate film, the drying of the coating composition, and the curing, (a) the first resin is readily present on the surface side of the release layer, resulting in a release layer with excellent peelability, which is therefore preferred.
[0131] Examples of aryl groups include phenyl, benzyl, tolyl, and xylyl, with phenyl being particularly preferred.
[0132] (a) The number-average molecular weight of the first resin is preferably 1,000 or more and less than 30,000, more preferably 2,000 or more and less than 15,000, and even more preferably 3,000 or more and less than 10,000. When the number-average molecular weight is 1,000 or more, it is easy to locally exist on the surface of the release layer, and sufficient peelability is easily obtained. On the other hand, when the number-average molecular weight is less than 30,000, there is a tendency for the emulsification properties of the silicone emulsion to become better and the uniform coating properties to become better. It should be noted that the number-average molecular weight in this invention refers to the molecular weight obtained by means of... 1 H NMR and 29 The peaks observed by Si NMR are used to identify the structure of siloxanes, and the values are calculated from the integral ratio of the peaks originating from each siloxane structure.
[0133] When the total solids content in the coating composition is set to 100 by weight, the content of the first resin contained in the silicone emulsion in the aqueous coating composition is preferably 5% by mass or more and 70% by mass or less, more preferably 7% by mass or more and 60% by mass or less, and even more preferably 10% by mass or more and 55% by mass or less. If it is 5% by mass or more, the amount of (a) first resin, which exhibits peelability by being locally present on the surface of the release layer, becomes sufficient, and the peelability is excellent, so it is preferred. When it is 70% by mass or less, there is no concern about re-peeling caused by an increase in uncrosslinked components, which is preferred. The amount of silicone emulsion in the aqueous coating composition can be appropriately adjusted so that the first resin is within the above-mentioned range.
[0134] It should be noted that, in this invention, the total solids weight in the coating composition forming the release layer refers to the total solids weight of (a), (b), (c), the substrate adhesion agent, and (d) used as needed.
[0135] (b) Second resin)
[0136] (b) The second resin containing hydrogen groups can be any compound having siloxane bonds in its main chain, preferably a polyorganosiloxane with hydrogen groups at the ends or on the side chains, and more preferably polydimethylsiloxane. The terminal silicon atoms may have hydrogen groups, but a trialkylsilane structure such as trimethylsilane is preferred, and it is even more desirable to have 2 or more but less than 50 hydrogen groups per molecule. Having 2 or more hydrogen groups results in a release layer with high crosslinking density during curing, exhibiting good peelability.
[0137] In one embodiment, the second resin may be exemplified by the structure shown in Chemical Formula 2 below.
[0138]
[0139] In Chemical Formula 2, l is 1 or more and 50 or less, m is 1 or more and 50 or less, and n is 0 or more and 5 or less. When l is 1 or more and 50 or less, the crosslinking reaction between the alkenyl and hydrogen groups in the coating composition proceeds, resulting in a release layer with high crosslinking density and excellent solvent resistance, which is therefore preferred. By making m 1 or more and 50 or less, the reaction delay during the curing of the release layer caused by the large volume of the phenyl group occurs, resulting in a release layer with good tensile follow-through and excellent adhesion, which is therefore preferred. In addition, the π electrons of the phenyl group interact with the substrate film, resulting in even better adhesion, which is therefore preferred. When n is 0 or more and 5 or less, the compatibility with (a) the first resin or (d) the fourth resin described later in the coating composition decreases, and (a) the first resin or (d) the fourth resin tends to be locally present on the surface side of the release layer. As a result, a release layer with excellent peelability is obtained, which is therefore preferred.
[0140] In this invention, the number-average molecular weight of the second resin (b) is preferably 1000 or more and less than 10000, more preferably 1000 or more and less than 5000, and even more preferably 1500 or more and less than 3000. When the number-average molecular weight is 1000 or more, sufficient peelability is easily obtained. On the other hand, when the number-average molecular weight is less than 10000, there is a tendency for the emulsification properties of the silicone emulsion to become better, and the coating uniformity to also become better. In addition, the crosslinking reaction can be carried out easily and effectively, the residual hydrogen groups in the release layer are reduced, and the peelability becomes better. It should be noted that the number-average molecular weight in this invention refers to the molecular weight obtained by... 1 H NMR and 29 The peaks observed by Si NMR are used to identify the structure of siloxanes, and the values are calculated from the integral ratio of the peaks originating from each siloxane structure.
[0141] When the total solids content in the coating composition is set to 100, the content of the second resin in the silicone emulsion of the aqueous coating composition is preferably 1% by mass or more and 50% by mass or less, more preferably 3% by mass or more and 40% by mass or less, and even more preferably 5% by mass or more and 35% by mass or less. A content of 1% by mass or more ensures sufficient crosslinking reaction, which is preferred. A content of 50% by mass or less eliminates concerns about increased unreacted components leading to re-peeling, which is also preferred.
[0142] The amount of silicone emulsion in the aqueous coating composition can be appropriately adjusted so that the second resin is within the range described above.
[0143] For example, in the case where the second resin in (b) contains an aryl group as shown in structural formula 2, when the total solid content in the coating composition is set to 100, the content of the second resin is equal to or less than the content of the third resin in (c) described later, and preferably the content of the second resin is less than 5% by mass less than the content of the third resin in (c) described later. By satisfying such conditions, the crosslinking reaction proceeds sufficiently, and there is no need to worry about the increase of unreacted components causing re-peeling, which is preferable.
[0144] The aryl-containing structure shown in Formula 2, when included in the second resin (b) compared to the first resin (a), further improves both adhesion and peelability, and is therefore preferred. Specifically, it is speculated that by including an aryl group in the second resin (b), which acts as a crosslinking agent, the compatibility with the first resin (a) is reduced. During the stretching of the substrate film or the drying and curing of the coating composition, (a) tends to be locally present on the surface side of the release layer, thus improving peelability. On the other hand, in the present invention, the curing reaction caused by the aryl group contained in the second resin (b), which acts as a crosslinking agent, can be appropriately controlled, and the adhesion is also improved due to the increased interaction between the substrate film and the release layer. Thus, according to the present invention, the conventional problems of excessively delayed curing reaction leading to the time required for curing of the release layer, and the inability to obtain the desired release layer due to rapid curing reaction, can be solved.
[0145] In another manner, the aryl-containing structure shown in Structural Formula 2 can exist in both (a) the first resin and (b) the second resin.
[0146] (c) Third resin)
[0147] In the silicone emulsion of the aqueous coating composition of the present invention, it is preferable to contain (c) a third resin, said (c) a third resin comprising SiO 4 / 2The Q unit shown is an organosilicon. An organosilicon emulsion containing (c) the third resin is formed by dispersing an organosilicon with this structure into an emulsion, colloid, or the like, in water. As an organosilicon with this structure, any compound having a siloxane bond in the main chain can have any structure, but polyorganosilicones with alkenyl groups at the ends and / or on the side chains are preferred. Furthermore, copolymers containing dialkylsiloxane units or alkylphenylsiloxane units exhibit exfoliability and allow for easy adjustment of the alkenyl group content in one molecule, and are therefore preferred. The terminal silicon atom preferably has an alkenyl group, but it can also be a trialkylsilane structure such as trimethylsilane.
[0148] As having SiO 4 / 2 The organosilicon of the Q unit shown can be exemplified by the structure shown in Chemical Formula 3 below.
[0149] R4 a R5 b SiO (4-a-b) / 2 …(Chemical Formula 3)
[0150] (In chemical formula 3, R4 is an alkenyl group with 2 to 8 carbon atoms, R5 is a monovalent saturated hydrocarbon group with 1 to 16 carbon atoms selected from alkyl or aryl groups, a is 0 to 3, b is 0 to 3, and each represents an integer satisfying a+b≤3.)
[0151] Here, chemical formula 3 represents the general formula, and the structural units a=0 and b=0 are called Q units. (c) The third resin has this Q unit. Additionally, structural units a=1 or a=2 can be siloxane structures with an alkenyl group, and structural units b=2 can be siloxane structures with only alkyl or aryl groups in the side chains. These siloxane structures are also possible. It should be noted that structural units a+b=3 represent siloxane structures with terminal groups.
[0152] Examples of alkenyl groups with 2 to 8 carbon atoms as represented by R4 include vinyl, allyl, butenyl, pentenyl, and hexenyl, among which vinyl is particularly preferred. Examples of alkyl groups as represented by R5 include methyl, ethyl, propyl, and butyl, while examples of aryl groups include phenyl and tolyl. From the viewpoint of reactivity with hydrogen groups, it is preferable that an alkenyl group with 2 to 8 carbon atoms as represented by R4 is included in (c). The fewer the number of carbon atoms, the less the influence of steric hindrance, and the better the reactivity; therefore, a vinyl group with 2 carbon atoms is preferred, and most preferably preferred. From the viewpoint of easy stripping, it is preferable that 50 mol% or more of the substituent in R5 is methyl.
[0153] Organosilicones with Q units can adopt a structure with three-dimensionally expanded siloxane bonds, thus the alkenyl groups in the molecule can also exist in a three-dimensionally expanded manner. Therefore, by reacting the second resin (b), which is an organosilicon with hydrogen groups, with the alkenyl groups in the molecule of (c), a dense cross-linked structure can be obtained, resulting in a release layer with excellent solvent resistance. Typically, the SiO2 contained in the release layer... 2 / 2 When the ratio of D units increases, the siloxane bonds readily acquire a helical structure. For example, in the case of polydimethylsiloxane, both methyl groups present in the siloxane bond are arranged on the outer side of the molecular chain, thus exhibiting hydrophobicity. On the other hand, when the ratio of Q units in the release layer increases, the helical structure of the siloxane bonds formed by the D units is disrupted, thus reducing hydrophobicity. Although there is no particular limitation in theory, by fabricating a release layer containing organosilicon with Q units, it is possible to achieve both the light peelability resulting from increased crosslinking density and the reduced hydrophobicity resulting from the disruption of the helical structure of the siloxane bonds, i.e., excellent wettability.
[0154] When the total solids content in the coating composition is set to 100, the content of the third resin (c) in the silicone emulsion of the aqueous coating composition is 10% by mass or more and 70% by mass or less, more preferably 15% by mass or more and 65% by mass or less, and even more preferably 20% by mass or more and 60% by mass or less. When it is 10% by mass or more, the helical structure of the silicone containing D units in the release layer is disrupted by the silicone having Q units, resulting in a release layer with excellent wettability, which is therefore preferred. When it is 70% by mass or less, the helical structure of the silicone containing D units in the release layer is not excessively disrupted by the silicone having Q units, resulting in a release layer with excellent peelability, which is therefore preferred.
[0155] The content of Si atoms in the Q unit relative to that of SiO 4 / 2 The total Si atoms in the organosilicon of the Q unit shown are 0.05 to 60 mol%, preferably 0.1 to 55 mol%, and more preferably 1.0 to 50 mol%. When the Si atom content in the Q unit is 0.05 mol% or more, a three-dimensionally expanded siloxane bond structure is sufficiently formed, exhibiting an effect of increasing crosslinking density, and is therefore preferred. If 60 mol% or less, even if excessive wettability is imparted, there is no concern about causing re-peeling, which is also preferred.
[0156] Furthermore, from the viewpoint of forming a dense cross-linked structure resulting from the reaction with the second resin (b), the content of Si atoms in the alkenyl siloxane structure is relative to that in the SiO structure. 4 / 2 The total Si atoms in the organosilicon of the Q unit shown are preferably 0.1 to 30 mol%, more preferably 1 to 20 mol%.
[0157] Organosilicones containing Q units are preferably solid at room temperature. Organosilicones containing Q units that are solid at room temperature mean that the Q units within the molecule exist in large quantities as continuous bonds, resulting in an organosilicon with a rigid molecular skeleton and exhibiting properties close to those of glass. By fabricating a release layer containing such a rigid molecular skeleton, the elastic modulus of the release layer is increased, making it less prone to deformation when peeling off objects such as ceramic green sheets, thus becoming a release layer exhibiting light peelability, which is therefore preferred.
[0158] As described above, silicones with Q units lack stretchability due to their rigid molecular backbone, potentially leading to coating cracking and reduced substrate adhesion due to stretching. However, in this invention, since an aryl-containing silicone emulsion as shown in Formula 2 is used as the coating composition, the crosslinking reaction is difficult to occur during substrate film stretching due to its reaction delay effect. Even with a release layer containing silicones with Q units, a release layer with strong adhesion and no coating defects can be formed. Furthermore, since a substrate adhesion promoter is included, a release layer with excellent immediate adhesion to the substrate can be formed.
[0159] (d) Fourth resin)
[0160] By including (d) a fourth resin with alkenyl groups only at both ends in the silicone emulsion of the aqueous coating composition of the present invention, it is also possible to obtain a release film that has excellent peelability, wettability, and substrate adhesion.
[0161] As the fourth resin (d), the resin exemplified by the following chemical formula 4 can be cited.
[0162]
[0163] In chemical formula 4, R1 is an alkenyl group with 2 to 8 carbon atoms, and p is 1 or more and 300 or less. By making p within the above range, it exhibits excellent peelability and is therefore preferred. (d) The fourth resin has alkenyl groups only at both ends, thus forming a linear structure with D units linked together. Therefore, the helical structure is not destroyed by the crosslinking reaction, and it exhibits better peelability than the first resin (a).
[0164] However, in the case of a fourth resin containing alkenyl groups only at the molecular ends, the amount of alkenyl groups is less than that of the first resin (a), and therefore the crosslinking density may be reduced. However, by crosslinking with the first silicone resin (a) which also has alkenyl groups in the side chains and is present in the release layer, the deterioration of solvent resistance can be prevented. Although not particularly limited in theory, the release film of the present invention contains a fourth silicone resin (d) containing alkenyl groups only at both ends in a localized area on the surface of the release layer. With the aid of the first silicone resin (a) which has alkenyl groups in the side chains, a release layer bonded to the silicone resin (c) having Q units and alkenyl groups is formed, thereby achieving a release layer with excellent peelability.
[0165] The number-average molecular weight of the fourth resin contained in the silicone emulsion of the present invention is preferably 1,000 or more and less than 10,000, more preferably 1,000 or more and less than 5,000, and even more preferably 1,500 or more and less than 3,000. When the number-average molecular weight is 1,000 or more, sufficient peelability is easily obtained. On the other hand, when the number-average molecular weight is less than 10,000, there is a tendency for the emulsification properties of the silicone emulsion to become better and the coating uniformity to become better. Furthermore, the crosslinking reaction can be carried out easily and effectively, the residual hydrogen groups in the release layer are reduced, and the peelability becomes better. It should be noted that the number-average molecular weight in the present invention refers to the molecular weight obtained by... 1 H NMR and 29 The peaks observed by Si NMR are used to identify the structure of siloxanes, and the values are calculated from the integral ratio of the peaks originating from each siloxane structure.
[0166] When the total solids content in the coating composition is set to 100, the content of the fourth resin in the silicone emulsion of the aqueous coating composition is preferably 1% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 40% by mass or less, and even more preferably 10% by mass or more and 35% by mass or less. A content of 1% by mass or more allows for localized presence on the surface of the release layer, thus exhibiting peelability, and is therefore preferred. A content of 50% by mass or less eliminates concerns about a decrease in the crosslinking density of the release layer leading to re-peeling, which is also preferred.
[0167] The amount of silicone emulsion in the aqueous coating composition can be appropriately adjusted so that the fourth resin is within the above-mentioned range.
[0168] (Substrate adhesion agent)
[0169] In this invention, there are no particular limitations on the substrate bonding agent, but a substrate bonding agent having the following structure is preferred: a hydrolyzable group and an organic functional group that are directly or by means of a linking group bonded to silicon atoms, and more preferably a water-soluble and / or water-dispersible silane coupling agent.
[0170] Substrate adhesion agents can be exemplified by compounds represented by the following chemical formulas.
[0171] YSiX3 (Chemical Formula 5)
[0172] Here, Y can be a functional group such as vinyl, epoxy, isocyanurate, mercapto, amino, methacryloyl, styrene, acryloyl, isocyanate, anhydride, or carboxyl. Y is particularly preferably epoxy, vinyl, or carboxyl. Y can be directly bonded to the Si element, or it can be bonded to the Si element by means of alkyl, ether, or oxoalkylene groups with 1 to 10 carbon atoms.
[0173] X is a hydrolyzable group such as methylene, ethylene, propylene, or alkylene, or methoxy, ethoxy, acetoxy, etc., and at least one of the three X's is a hydrolyzable group, preferably all three X's are hydrolyzable groups. Methoxy and ethoxy are preferred as hydrolyzable groups.
[0174] Examples of preferred substrate bonding agents include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, and vinylmethyldimethoxysilane.
[0175] Two or more substrate adhesion promoters can be used. When two or more water-soluble or water-dispersible organosilane coupling agents are used together, it is preferable that the agent has at least a structure containing a vinyl group in Y in chemical formula 5, and more preferably a combination of a silane coupling agent with an epoxy group introduced in Y and a silane coupling agent with a vinyl group introduced in Y. By having a structure with a vinyl group introduced in Y, the release layer can react with the silane coupling agent, resulting in excellent substrate adhesion, especially immediate adhesion to the substrate, which is therefore preferred. By using a silane coupling agent with an epoxy group introduced in Y and a silane coupling agent with a vinyl group introduced in Y together, for example, the silane coupling agent containing an epoxy group adheres to the substrate side, and the silane coupling agent containing a vinyl group forms a crosslinking reaction with the release layer, thus providing excellent immediate adhesion to the substrate, which is also preferred.
[0176] The content of the adhesive agent in the substrate is preferably 0.01 parts by mass or more and 15 parts by mass or less when the total solid content forming the release layer is set to 100 parts by mass, more preferably 0.05 parts by mass or more and 10 parts by mass or less, and most preferably 0.1 parts by mass or more and 8 parts by mass or less. If the content of the adhesive agent is 0.01 parts by mass or more and 15 parts by mass or less, the substrate adhesion of the release layer, especially the immediate adhesion to the substrate, becomes good.
[0177] At this point, the total solids weight of the release layer refers to the total solids weight of (a), (b), (c), the substrate adhesive agent, and (d) used as needed.
[0178] (surfactant)
[0179] The aqueous coating composition of the present invention preferably contains a surfactant. The presence of a surfactant results in excellent coatability when coating the coating composition onto a polyester film, which serves as the substrate film, eliminating concerns about coating defects such as pinholes, which is preferable. Furthermore, it does not impair the stability of the emulsion present in the coating composition, eliminating concerns about aggregates or gels from the coating composition being incorporated into the release layer, and suppressing unevenness and non-uniform coating in the release layer, thus making it preferable.
[0180] In the presence of surfactants, during the drying and curing process of the aqueous coating composition applied to the substrate, the surfactants segregate on the substrate side, sometimes deteriorating the substrate adhesion. However, in this application, since an aqueous coating composition containing a substrate adhesion promoter is used, it is possible to form a release layer in which the substrate adhesion does not deteriorate.
[0181] As a surfactant, known materials can be used without particular restrictions, but materials that retain surfactant residue in the release layer by suppressing surfactant volatilization during the heating process of stretching and crystallizing the substrate film are preferred. The presence of surfactant residue in the release layer improves wettability to ceramic slurries and the like using organic solvents, and is therefore preferred.
[0182] As surfactants, cationic, anionic, and nonionic surfactants are preferred, with nonionic surfactants being preferred from the viewpoint of improving emulsion stability. Examples include at least one type selected from alkylene oxide adducts of higher alcohols and / or higher fatty acids, esters of alkylene oxide adducts of higher fatty acids and alcohols, alkylene oxide adducts of alkanolamides, alkylene oxide adducts of sorbitol esters, and alkylene oxide adducts of higher fatty acid glycerides. The surfactant used preferably has an HLB value in the range of 6 to 18. Here, the HLB value is calculated according to Griffin's formula.
[0183] Examples of epoxy alkane include ethylene oxide, propylene oxide, and butane oxide; one or more of these can be used. When using multiple types, regardless of whether they are block or random addition forms, the HLB value is preferably in the range of 8 to 18, and more preferably in the range of 10 to 15. Examples of these nonionic emulsifiers include polyoxyethylene lauryl ether and polyoxyethylene tridecyl ether. When using nonionic emulsifiers with HLB values outside this range as emulsifiers for organosilicon aqueous dispersions, the emulsifying and dispersing power and the stability of the aqueous dispersion may sometimes decrease.
[0184] As an example of the epoxide used in this invention, the structure shown in Chemical Formula 6 below can be exemplified.
[0185] H 2m+1 C m -O-(CH2-CH2-O) n -H (Chemical Formula 6)
[0186] (In chemical formula 6, m and n are integers from 1 to 30. The number m represents the alkyl chain length, and the number n represents the number of moles of ethylene oxide added.)
[0187] A higher m number indicates a longer alkyl chain, resulting in better oleophilicity and superior stability of the aqueous silicone emulsion, which is preferred. Conversely, a higher n number indicates a greater amount of ethylene oxide, leading to better hydrophilicity and improved stability of the aqueous silicone emulsion, which is also preferred. The m and n numbers can take any value from 1 to 30, but higher values result in higher molecular weights. This prevents surfactant volatilization during the heating and curing process of the coating composition and the stretching and crystallization process of the substrate film, thus avoiding contamination of the release film manufacturing process, which is also preferred.
[0188] The surfactant content in the aqueous coating composition is preferably 0.1 to 20 parts by weight, more preferably 0.15 to 15 parts by weight, when the total solid content forming the release layer is set to 100 parts by weight. A content of 0.1 parts by weight or more results in excellent coatability when coated onto a polyester film, and is therefore preferred. A content of 20 parts by weight or less is preferred because there is no concern about excessive residual surfactant causing a decrease in substrate adhesion.
[0189] At this point, the total solids weight of the release layer refers to the total solids weight of (a), (b), (c), the bonding agent, and (d) used as needed.
[0190] (Catalyst solidification)
[0191] In the aqueous coating composition of the present invention, a platinum-based catalyst is required to enable the addition reaction between the alkenyl-based organosilicon and the hydrogen-based organosilicon. Known catalysts can be used as platinum-based catalysts, such as platinum chloride and chloroplatinic acid. Considering dispersibility in the organosilicon, the platinum-based catalyst can be a platinum(O)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex (Karstedt catalyst), which ensures uniform dispersion by simultaneously dispersing it during organosilicon emulsification.
[0192] The amount of platinum-based catalyst is preferably in the range of 10 to 800 ppm by weight of platinum relative to the total solid content forming the release layer. By setting it within this range, the organosilicon can be sufficiently cured, and the formation of aggregates can be suppressed, resulting in a release film with excellent smoothness. When the weight ratio of platinum is 800 ppm or less, there is no concern about the accelerated addition reaction between alkenyl and hydrogen groups leading to the formation of organosilicon aggregates, which is preferable. The amount of platinum-based catalyst is more preferably 600 ppm or less, further preferably 500 ppm or less, and most suitablely 300 ppm or less. Furthermore, when it is 10 ppm or more, the organosilicon addition reaction proceeds effectively, the curing of the release layer becomes sufficient, and it exhibits light peelability, which is therefore preferable.
[0193] In the aqueous coating composition of the present invention, a reaction inhibitor is preferably contained to suppress the activity of the platinum-based catalyst at room temperature. The content of the reaction inhibitor relative to the total weight of the aqueous coating composition is preferably 5 to 1000 ppm, more preferably 10 to 700 ppm, and most preferably 20 to 500 ppm. If it is 5 ppm or more, the effect of suppressing the activity of the platinum-based catalyst becomes sufficient, which is preferable. If it is 1000 ppm or less, there is no concern about the interior of the oven being contaminated by the reaction inhibitor volatilized during heat treatment, which is preferable.
[0194] Colorants, ultraviolet absorbers, particles, etc., may be further added to the aqueous coating composition of the present invention without prejudice to the subject matter of the present invention.
[0195] (Characteristics of other release layers)
[0196] The thickness of the release layer in this invention, measured by its thickness after drying and curing, is preferably 0.001 to 0.2 μm, more preferably 0.005 to 0.1 μm. A thickness of 0.001 μm or more results in a release layer with excellent peelability, and is therefore preferred. A thickness of 0.2 μm or less eliminates the need to increase the solid content concentration and coating amount of the release layer component in the aqueous coating composition, resulting in excellent coatability when coated onto the substrate film, and is therefore preferred.
[0197] (Method for manufacturing release film)
[0198] In one embodiment, a release layer is formed on at least one side of the substrate film. For the release layer, after an aqueous coating composition is applied to the substrate film, heat drying is performed to form a release layer by reacting and curing the components in the aqueous coating composition. This release layer is preferably formed during the film-forming process.
[0199] When coating an aqueous coating composition onto a substrate film, the concentration of the solid component in the aqueous coating composition is preferably 20% by mass or less, more preferably 1% by mass or more and 10% by mass or less. If the concentration of the solid component of the release layer component in the aqueous coating composition is above the lower limit, the film-forming properties tend to improve. Furthermore, if the concentration of the solid component is below the upper limit, the stability of the aqueous coating composition and the appearance of the release layer tend to improve. Water is preferably used as the aqueous solvent for adjusting the concentration of the solid component.
[0200] The aqueous coating composition applied to the substrate film to form a release layer can be applied at any stage, but is preferably applied during the manufacturing process of the polyester film, and more preferably applied to the polyester film before orientation and crystallization are complete. Then, after stretching in at least one direction, heat treatment can be performed to complete the crystal orientation.
[0201] Here, polyester films before crystal orientation is completed include: unstretched films, or uniaxially oriented films in which the unstretched films are oriented in either the longitudinal direction (hereinafter, sometimes referred to as the film continuous film-making direction, length direction, MD direction) or the transverse direction (hereinafter, sometimes referred to as the direction orthogonal to the longitudinal direction, width direction, TD direction), and films that are then low-ratio stretched and oriented in both the longitudinal and transverse directions (biaxially stretched films before orientation crystallization is completed by re-stretching in the longitudinal or transverse direction).
[0202] Preferably, an aqueous coating composition is applied to an unstretched film or a uniaxially stretched film oriented in one direction, followed by direct longitudinal stretching and / or transverse stretching and heat setting—a process known as in-line coating. The release layer can be dried by a stretching process or heat setting after coating, or a further drying process can be applied as needed. Alternatively, if a cured film is obtained by using a catalyst to cure the composition, it can be cured by a stretching process or heat setting, or a further curing process can be applied as needed.
[0203] Regarding the release layer in this invention, the determination of "coating an aqueous coating composition on an unstretched film or a uniaxially stretched film oriented in one direction, directly performing longitudinal stretching and / or transverse stretching, and thermal fixation" and the determination of "forming the release layer by an online coating method" are to determine the structure of the object through the manufacturing method. However, as described below, there are cases where the object cannot be directly determined by its structure or characteristics, or is almost impractical.
[0204] It is speculated that the aqueous coating composition forming the release layer in this invention, through longitudinal and / or transverse stretching together with the coated film, causes the first, second, and third resins contained in the silicone emulsion, as well as the fourth resin contained as needed, to oriented and interact.
[0205] For example, it is speculated that during the water drying process in the aqueous coating composition, during the stretching of the substrate film, or during the curing of the release layer, due to the difference in compatibility and molecular weight between the first resin, the second resin, and the third resin, (a) it is easy to be locally present on the surface side of the release layer, thus improving the peelability.
[0206] On the other hand, in this invention, the curing reaction caused by the aryl group contained in the second resin (b), which acts as a crosslinking agent, can be appropriately controlled, and the adhesion between the substrate film and the release layer is improved by increasing the interaction between them. Furthermore, the immediate adhesion of the substrate is also improved by the substrate adhesion promoter.
[0207] However, it is structurally difficult to determine the orientation and distribution of the resin components in the release layer, as well as the distribution of substituents that contribute to peelability on the surface of the release layer.
[0208] Furthermore, given the measurement techniques used at the time of this application, it is impossible or impractical to measure the structure or characteristics of the release film of this invention, analyze and determine its physical properties based on these results. Therefore, regarding this invention, at the time of application, there were situations where it was not possible, or almost impractical, to directly determine the object through its structure or characteristics.
[0209] As a coating method for water-based coating compositions, any known coating method can be applied. For example, roller coating, gravure coating, roller brush coating, spray coating, air knife coating, impregnation coating, curtain coating, etc., can be used alone or in combination.
[0210] In one embodiment, the manufacturing method of the present invention provides a method for manufacturing a release film for manufacturing resin sheets and multilayer ceramic capacitors.
[0211] (Resin sheet)
[0212] The resin sheet in this invention is not particularly limited as long as it is formed on the side of the release layer opposite to the substrate. Examples include resin sheets formed by curing a resin sheet composition containing resin components and a crosslinking agent, and resin sheets formed by molding film-forming organic components through melt film formation or solution film formation. In one embodiment, the release film of this invention is a release film for molding resin sheets containing inorganic compounds. Examples of inorganic compounds include metal particles, metal oxides, and minerals, such as calcium carbonate, silica particles, aluminum particles, and barium titanate particles. Because this invention has a release layer with high smoothness, even when these inorganic compounds are included in the resin sheet, it is possible to suppress defects that may be caused by inorganic compounds, such as resin sheet breakage and difficulty in peeling the resin sheet from the release layer.
[0213] The resin components forming the resin sheet can be appropriately selected according to the application. In one embodiment, the resin sheet containing an inorganic compound is a ceramic green sheet. For example, the ceramic green sheet may contain barium titanate as an inorganic compound. Alternatively, as a resin component, a polyvinyl butyral resin may be included, for example.
[0214] (Ceramic green sheets and ceramic capacitors)
[0215] Typically, a multilayer ceramic capacitor has a cuboid ceramic blank. Inside the ceramic blank, a first internal electrode and a second internal electrode are alternately arranged along the thickness direction. The first internal electrode is exposed at a first end face of the ceramic blank. A first external electrode is disposed on the first end face. The first internal electrode is electrically connected to the first external electrode at the first end face. The second internal electrode is exposed at a second end face of the ceramic blank. A second external electrode is disposed on the second end face. The second internal electrode is electrically connected to the second external electrode at the second end face.
[0216] In one embodiment, the release film of the present invention is a release film for manufacturing ceramic green sheets, used to manufacture such laminated ceramic capacitors.
[0217] For example, when using the release film for manufacturing ceramic green sheets according to the present invention, the ceramic green sheets are manufactured in the following manner: First, using the release film of the present invention as a carrier film, a ceramic slurry for forming a ceramic green body is coated and dried. A conductive layer for forming a first or second internal electrode is printed on the coated and dried ceramic green sheet. The ceramic green sheet, the ceramic green sheet with the conductive layer for forming the first internal electrode printed on it, and the ceramic green sheet with the conductive layer for forming the second internal electrode printed on it are appropriately stacked and pressed to obtain a master laminate. The master laminate is divided into multiple parts to produce unprocessed ceramic green bodies. A ceramic green body is obtained by firing the unprocessed ceramic green body. Then, by forming the first and second external electrodes, a multilayer ceramic capacitor can be completed.
[0218] Example
[0219] The present invention will now be described in more detail using examples, but the invention is not limited to these examples. The characteristic values used in the present invention are evaluated using the methods described below.
[0220] (Thickness of release layer)
[0221] After cutting the release film into small triangular pieces, a 2 nm thick Pt (platinum) layer was formed on the surface of the release layer by coating. The resulting sample was fixed in a multiaxial embedding capsule and embedded in epoxy resin. Using an ULTRACUT-S microtome, the sample was cut in a direction perpendicular to the film's surface to obtain an ultrathin sample with a height of 50 nm. Next, the ultrathin sample was placed on a grid and vapor-stained with 2% osmium tetroxide at 60 °C for 2 hours. Using the vapor-stained ultrathin sample, the film cross-section was observed using a LEM-2000 transmission electron microscope at an accelerating voltage of 100 kV to determine the thickness of the release layer. Measurements were taken at any 10 points, and their average value was taken as the thickness of the release layer.
[0222] (Uniformity of the release layer coating)
[0223] The release film obtained by rolling it into a roll is rolled out, cut into A4 sheets, and when visually observing the release layer using fluorescent and halogen lamps, the number of aggregated coating defects (number per A4 sheet) is compared and evaluated according to the following criteria.
[0224] ◎: No coating defects
[0225] 〇: 1-2 defective spots in the coating
[0226] △: 3-5 defective spots in the coating
[0227] ×: More than 6 defects in the coating.
[0228] (Adhesion to the substrate)
[0229] An A4-sized cut sample was evaluated after the release film roll, prepared by the method described in the following examples, was unwound within 30 minutes of winding. The release surface of the release film was rubbed five times with a thumb under a load of approximately 500 gf. To confirm the removal of silicone from the rubbed area, a writing test was performed using Magic Ink (manufactured by Teranishi Chemical Industry Co., Ltd., extra coarse, MGD-T2). The evaluation was based on the writing quality of the Magic Ink according to the following criteria.
[0230] ◎: There is no difference between the non-friction part and the friction part; both show Magic Ink shrinkage cavities.
[0231] 〇: There are differences between the non-friction part and the friction part, but both show Magic Ink shrinkage cavities.
[0232] △: A pore of Magic Ink was observed in a part of the friction section, most of which was wetted by Magic Ink.
[0233] ×: The entire friction part was wetted with Magic Ink, and no shrinkage cavities were observed.
[0234] (Surface free energy)
[0235] For samples conditioned at 23°C and 50%RH for 24 hours, the static contact angle was measured using a contact angle meter (DMo-501, Kyowa Interface Chemicals Co., Ltd.) after adding water and allowing it to stand for 30 seconds. Similarly, the static contact angles of ethylene glycol and diiodomethane were measured separately. Using the surface tension components of each liquid, the following simultaneous equations were established regarding the surface tension components of the release layer (the test solutions for water, ethylene glycol, and diiodomethane are designated as 1, 2, and 3 respectively; γLD is the dispersion force component of the liquid; γLP is the polar force component of the liquid; γLH is the hydrogen bonding component of the liquid; γL is the total value of all surface tension components in the liquid; γSD represents the dispersion force component of the release layer; γSP represents the polar force component of the release layer; γSH represents the hydrogen bonding component of the release layer; and θ represents the contact angle).
[0236] (γSD·γLD1) 1 / 2 +(γSP·γLP1) 1 / 2 +(γSH·γLH1) 1 / 2 =γL1(1+cosθ1) / 2
[0237] (γSD·γLD2) 1 / 2 +(γSP·γLP2) 1 / 2 +(γSH·γLH2) 1 / 2 =γL2(1+cosθ2) / 2
[0238] (γSD·γLD3) 1 / 2 +(γSP·γLP3) 1 / 2 +(γSH·γLH3) 1 / 2 =γL3(1+cosθ3) / 2
[0239] It should be noted that the γLD, γLP, γLH, and γL of water, ethylene glycol, and diiodomethane are shown in Table 1.
[0240] [Table 1]
[0241]
[0242] Next, based on the values of γSD, γSP and γSH obtained above, the surface free energy γS of the release layer surface is calculated using the following formula.
[0243] γS = γSD + γSP + γSH
[0244] (Ceramic sheet peelability)
[0245] Slurry composition I, consisting of the following materials, was stirred and mixed for 10 minutes, and then dispersed for 10 minutes using a bead mill with zirconia beads of 0.5 mm diameter to obtain a primary dispersion. Then, slurry composition II, containing the following materials, was added to the primary dispersion at a ratio of (slurry composition I): (slurry composition II) = 3.4:1.0, and dispersed a second time for 10 minutes using a bead mill with zirconia beads of 0.5 mm diameter to obtain a ceramic slurry.
[0246] (Slurry Composition I)
[0247] 22.3 parts by weight of toluene
[0248] 18.3 parts by weight of ethanol
[0249] Barium titanate (average particle size 100 nm) 57.5 parts by weight
[0250] HOMOGENOL L-18 (manufactured by Kao Corporation) 1.9 parts by weight
[0251] (Slurry Composition II)
[0252] 39.6 parts by weight of toluene
[0253] 39.6 parts by weight of ethanol
[0254] 3.3 parts by weight of dioctyl phthalate
[0255] Polyvinyl butyral (S-LEC BM-S, manufactured by Sekisui Chemicals Co., Ltd.) 16.3 parts by weight
[0256] 0.5 parts by weight of ethyl 1-ethyl-3-methylimidazolium sulfate
[0257] Next, using an applicator, the dried slurry was coated onto the release surface of an A4-cut sample, which was rolled up within 12 hours after being prepared as described in the following examples, to a thickness of 2.0 μm. The sample was dried at 60°C for 1 minute to obtain a release film with ceramic green sheets. After removing static electricity from the obtained release film with ceramic green sheets using a destaticator (KEYENCE CORPORATION, SJ-F020), a peel tester (Kyowa Interface Science Co., Ltd., VPA-3, load sensor load 0.1N) was used to peel the film at a peel angle of 90 degrees, a peel temperature of 60°C, and a peel speed of 0.3 m / min. As the peel direction, double-sided adhesive tape (Nitto Denko Co., Ltd., NO.535A) was attached to the SUS plate provided with the peel tester. The release film was fixed on the tape by adhering it to the release film side, and peeling was performed by stretching the ceramic green sheet side. From the obtained measurements, the average peel force for peel distances of 20mm to 70mm was calculated and taken as the peel force. A total of five measurements were performed, and the average peel force was used for evaluation. The obtained peel force values were judged according to the following criteria.
[0258] ◎: Less than 1.0 mN / mm
[0259] 〇: Above 1.0 mN / mm and less than 2.0 mN / mm
[0260] △: 2.0mN / mm or more
[0261] ×: The ceramic piece cannot be peeled off or breaks during peeling.
[0262] (Organosilicon emulsion: a-1)
[0263] Using an emulsification device (manufactured by NP-Lab Co., Ltd., device name "Ultraplanetary Mixer") capable of stirring the entire container, a raw material containing 98% by mass of alkenyl organosilicon (o=125, k=4, number-average molecular weight 9756) as shown in chemical formula (a-1) and 2% by mass of polyoxyethylene lauryl ether (manufactured by Kao Corporation, trade name "EMULGEN 109P") as a surfactant was mechanically emulsified in an aqueous medium to obtain an organosilicon emulsion (a-1) with a solid content of 20% by mass. Furthermore, the emulsion particle size was adjusted by regulating the stirring speed and stirring time during emulsification.
[0264]
[0265] (Organosilicon emulsion: b-1)
[0266] Using an emulsification device (manufactured by NP-Lab Co., Ltd., device name "Ultraplanetary Mixer") capable of stirring the entire container, a raw material containing 98% by mass of an organosilicon (l=21, m=8, n=4, number-average molecular weight 2806) with hydrogen groups and phenyl groups as shown in chemical formula (b-1) and 2% by mass of polyoxyethylene lauryl ether (manufactured by Kao Corporation, trade name "EMULGEN 109P") as a surfactant was mechanically emulsified in an aqueous medium to obtain an organosilicon emulsion (b-1) with a solid content of 20% by mass. Furthermore, the emulsion particle size was adjusted by regulating the stirring speed and stirring time during emulsification.
[0267]
[0268] (Organosilicon emulsion: b-2)
[0269] Using an emulsification device (manufactured by NP-Lab Co., Ltd., device name "Ultraplanetary Mixer") capable of stirring the entire container, a raw material containing 98% by mass of an organosilicon (l=40, n=40, number-average molecular weight 5522) with hydrogen groups and phenyl groups as shown in chemical formula (b-2) and 2% by mass of polyoxyethylene lauryl ether (manufactured by Kao Corporation, trade name "EMULGEN 109P") as a surfactant was mechanically emulsified in an aqueous medium to obtain an organosilicon emulsion (b-2) with a solid content of 20% by mass. Furthermore, the emulsion particle size was adjusted by regulating the stirring speed and stirring time during emulsification.
[0270]
[0271] (Organosilicon emulsion: c-1)
[0272] Using an emulsifying device (manufactured by NP-Lab Co., Ltd., device name "Ultraplanetary Mixer") capable of stirring the entire contents of the container, an emulsifier containing 98% by mass of SiO2 was created. 4 / 2 The organosilicon of the Q unit shown and 2% by mass of polyoxyethylene lauryl ether (manufactured by Kao Corporation, trade name "EMULGEN 109P") as a surfactant were mechanically emulsified in an aqueous medium to obtain an organosilicon emulsion (c-1) containing organosilicon with Q units and a solid content of 20% by mass. At this time, SiO 4 / 2 The organosilicon of the Q unit shown is represented by chemical formula 3 as the general formula, where R4 is vinyl and R5 is methyl. Only one vinyl atom is bonded to the Si atom directly bonded to the vinyl group. The Si atom bonded to the vinyl group has SiO2 content relative to the SiO2 group. 4 / 2The total Si atom content in the organosilicon of the Q unit shown is 5 mol%, and the Si atom content in the Q unit is 40 mol%. That is, in chemical formula 3, there are 5 mol% of siloxane structures with R4 being vinyl, R5 being methyl, a=1, and b=1, 40 mol% of siloxane structures with a=0 and b=0, and 55 mol% of siloxane structures with R5 being methyl, a=0, and b=2 or 3. Furthermore, the emulsion particle size is adjusted by adjusting the stirring speed and stirring time during emulsification. Additionally, the adjustment is made so that the number average molecular weight is 200,000.
[0273] R4 a R5 b SiO (4-a-b) / 2 …(Chemical Formula 3)
[0274] (In chemical formula 3, R4 is an alkenyl group with 2 to 8 carbon atoms, R5 is a monovalent saturated hydrocarbon group with 1 to 16 carbon atoms selected from alkyl or aryl groups, a is 0 to 3, b is 0 to 3, and each represents an integer satisfying a+b≤3.)
[0275] (Organosilicon emulsion: d-1)
[0276] Using an emulsification device (manufactured by NP-Lab Co., Ltd., device name "Ultraplanetary Mixer") capable of stirring the entire container, a raw material containing 98% by mass of an organosilicon (p=23, number-average molecular weight 1888) with alkenyl groups only at both ends as shown in chemical formula (d-1) and 2% by mass of polyoxyethylene lauryl ether (manufactured by Kao Corporation, trade name "EMULGEN 109P") as a surfactant was mechanically emulsified in an aqueous medium to obtain an organosilicon emulsion (d-1) with a solid content of 20% by mass. Furthermore, the emulsion particle size was adjusted by regulating the stirring speed and stirring time during emulsification.
[0277]
[0278] (Substrate adhesion agent: e-1)
[0279] A mixture of 3-glycidoxypropyltrimethoxysilane and triacetoxyvinylsilane in a weight ratio of 1:1 was used.
[0280] (Substrate adhesion agent: e-2)
[0281] Use triacetoxyvinylsilane.
[0282] <Example 1 of the manufacture of waterborne coating compositions>
[0283] Silicone emulsions (a-1), (b-1), (c-1), (d-1), substrate adhesion promoter (e-1), and water were mixed at the ratios described in Table 2, with a solid content concentration of 4% by mass, to obtain an aqueous coating composition. At this time, relative to the total weight of the aqueous coating composition, 0.02% by mass of a platinum-based catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: CAT-PM-10A) and 150 ppm of a crosslinking reaction inhibitor (1-ethynylcyclohexanol) were mixed and used.
[0284] <Examples 2-8 of the manufacture of water-based coating compositions>
[0285] The water-based coating composition was obtained by mixing in the manner and ratios described in Table 2, except that the method was the same as that used in Manufacturing Example 1.
[0286] <Example 1>
[0287] Polyethylene terephthalate ([η] = 0.63 dl / g, Tg = 78 °C) containing 0.25% by mass of calcium carbonate particles with an average particle size of 0.6 μm was melted in an extruder, passed through a filter with a filtration precision of 10 μm, extruded from a die, and cooled on a cooling drum using conventional methods to produce an unstretched film. Next, the film was stretched longitudinally to 3.2 times its original length at 80 °C, and the aqueous coating composition obtained in Manufacturing Example 1 was uniformly coated onto one surface of the polyester film using a roller coater. The coated film was then dried at 115 °C, stretched transversely to 4.0 times its original length at 145 °C, and further heat-fixed at 230 °C for approximately 10 seconds to ensure the crystal orientation of the substrate film. The film was then wound into a roll to obtain a roll of release film (25 μm thick) having the release layer shown in Table 2. Samples of the release film rolled from the obtained release film roll and cut into A4 size were evaluated as described in Table 2. It should be noted that the coating amount of the water-based coating composition is applied in such a way that the thickness of the cured and stretched release layer is the same as the thickness recorded in Table 2.
[0288] <Examples 2-8>
[0289] Using the aqueous coating composition obtained in the manufacturing example described in Table 2, a release film was obtained by the same method as in Example 1.
[0290] <Comparative Examples 1-2>
[0291] Using the aqueous coating composition obtained in the manufacturing example described in Table 2, a release film was obtained by the same method as in Example 1.
[0292] As shown in Table 2, in Examples 1 to 8, release films with excellent coating uniformity, immediate adhesion to the substrate, and ceramic sheet peelability were obtained.
[0293] In contrast, in Comparative Example 1, because an aqueous coating composition without (c) silicone having Q units was used to form the release layer, the crosslinking density of the release layer was insufficient, resulting in poor peelability. Furthermore, the immediate adhesion to the substrate was poor. In Comparative Example 2, because an aqueous coating composition without an adhesion promoter was used to form the release layer, the immediate adhesion to the substrate was also poor. Defects were observed in the release layer during the manufacturing process, including transfer of the release layer to the roller and transfer of the release layer to the back side of the release film during winding, making it impossible to peel off the ceramic sheet.
[0294] [Table 2]
[0295]
[0296] Industrial availability
[0297] The release film of the present invention has high peelability and wettability of the release layer, high adhesion between the substrate film and the release layer, especially high instant adhesion to the substrate, and the release layer is not easy to fall off. Therefore, it can suppress the generation of defects when forming thin resin sheets, especially ceramic green sheets.
Claims
1. A release film having a release layer on at least one side of a polyester film, The release layer is a layer formed by reacting and curing the water-based coating composition. The aqueous coating composition contains an organosilicon emulsion comprising the following resins. The aqueous coating composition also contains a substrate adhesion promoter. (a) A first resin having a siloxane structure as shown in Formula 1, In structural formula 1, R1 is an alkenyl group with 2 or more carbon atoms and less than 8 carbon atoms, R2 is an alkyl group with 1 to 4 carbon atoms or an alkenyl group with 2 or more carbon atoms and less than 8 carbon atoms, and k is 1 or more and less than 50. (b) The second resin, which contains hydrogen groups; and (c) The third resin, which contains SiO 4 / 2 The Q unit shown is an organosilicon.
2. The release film according to claim 1, wherein, The substrate bonding agent is a water-soluble or water-dispersible silane coupling agent, which has hydrolyzable groups and organic functional groups directly or by means of linking groups bonded to silicon atoms.
3. The release film according to claim 1, wherein, The (a) first resin and / or the (b) second resin also have a siloxane structure as shown in structural formula 2 below. In structural formula 2, R3 is an alkyl group with 1 to 4 carbon atoms, Ar is an aryl group, and m is 1 or more and 50 or less.
4. The release film according to claim 1, wherein, The second resin (b) has the structure shown in chemical formula 2 below. In chemical formula 2, l is greater than or equal to 1 and less than or equal to 50, m is greater than or equal to 1 and less than or equal to 50, and n is greater than or equal to 0 and less than or equal to 5.
5. The release film according to claim 1, wherein, The release film is formed as follows: the aqueous coating composition is coated on a substrate film before crystal orientation is completed, stretched in at least one direction, and then heat-treated to complete the crystal orientation of the substrate film.
6. The release film according to claim 1, wherein, The release film is a release film used in the manufacture of ceramic capacitors or resin sheets.
Citation Information
Patent Citations
Method of and apparatus for drying grain
JP1982035278A
Manufacture of hydrothermally synthetic substance
JP1982056315A
Polysiloxane coating material and releasing film
JP2003292894A
Silicone release polyester film
JP2021011081A
Mold release film
WO2017200056A1